(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Many cultures and mythologies worldwide since ages have mentioned and discussed the existence of androgyny in addition and equivalence to the existence of male and female genders. Androgyny refers to the existence of both male and female characteristics as well as anatomy in the same body or person. An androgynous body is a definite kind of body that contains both female and male organs and hence cannot be classified as either male or female and is considered intersex and ambiguous.